Assessing the African armyworm - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The African armyworm is the caterpillar of the moth Spodoptera exempta which occurs mainly in Africa. It feeds almost exclusively on cereals and grasses and occasionally on sedges. It is a serious pest of maize, sorghum, millet, rice and wheat and,...